Blacklisting and its legacy in the UK construction industry: employment relations in the aftermath of exposure of the Consulting Association. Issue 3 (26th April 2016) - Druker, Janet
Abstract: This paper explores responses to the exposure of blacklisting in the UK construction industry in the period following the closure of the Consulting Association (CA) in 2009. It asks whether employer collusion to blacklist in this way has been terminated and concludes that it is now largely of historical interest although other forms of anti‐union activity continue. It highlights particularly the historic and continuing importance of 'double breasting' and reports on divergent employer paths in the aftermath of the exposure and subsequent closure of the activities of the CA.